TEACHING LISTENING COMPREHENSION THROUGH PICTURE DICTATION TO THE TENTH GRADE STUDENTS OF SMA ISLAM AZ ZAHRA PALEMBANG - Khairunnisa Dwinalida; Zainal Abidin Naning; Hariswan Putra Jaya (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2014)
Abstract: This article reports the results of the study that was aimed to answer whether or not using picture dictation can improve the listening comprehension of the tenth grade students of SMA Islam Az-Zahra Palembang.The population of this study was the tenth grade students of SMA Islam Az-Zahra Palembang, in academic year 2013-2014 (N=52). The sample was selected by using total sampling. To collect the data, a picture dictation test witha multiple choice form (N of test item = 35). Paired sample and independent t-test were applied to analyze the data.The results of the paired sample t-test showed that there was significant difference in listening comprehension before and after the treatment in experimental. The results of independent sample t-test showed that there was improvement in listening comprehension achievement of the students who were taught through picture dictation. Key words: Listening comprehension, Picture Dictation, tenth graders